Pemikiran Muhammad Abdul Mannan Tentang Produksi - Fita Nurotul Faizah (LPMP Imperium, 2019)
Purpose-This research explains how production-based economy prosperity thinking of Muhammad Abdul Mannan’s perspective. Methods- This research is a library research that seeks to dissect the work of Muhammad Abdul Mannan in Islamic Economic; Theory and Practice with descriptive and explorative qualitative methods based on a sociological-historical approach and analyzed by deduction. Findings- The results show that the existence of production is present along with human needs. The goal of production is profit oriented and spiritual oriented. To achieve these are required factors of productions that include: land, labor, capital and organization. Mannan stressed that production activities should be based on economic welfare. Welfare indicators according to Mannan is in the form of increase revenue caused by the increased production of the utilization of resources to the maximum, good human resources as well as natural resources in the production process hereinafter with objective indicators. Whereas, the second indicator in the form of welfare that is subjective is the activity of production which is based on provisions of the shari'ah Implications/limitations – this research can make a positive contribution to the continuation of the concept of production as supporting the economic welfare of the community in order to participate in improving the economic State.